2016
DOI: 10.1017/s000748531600002x
|View full text |Cite
|
Sign up to set email alerts
|

Chlorpyrifos-induced hormesis in insecticide-resistant and -susceptible Plutella xylostella under normal and high temperatures

Abstract: Hormesis induced by insecticides at the dosage lower than what ostensibly directly causes death on insects was studied. This paper reports the effects of the in vivo application of varied concentrations of chlorpyrifos (CPF) on Plutella xylostella (DBM). The insecticide concentrations applied included 0.000025-2.5 mg l-1, which are far lower than LC1 (7.2 mg l-1), for the CPF-susceptable (Si) DBM, and 250 mg l-1 which is far below LC1 (1286 mg l-1), for the CPF-resistant (Rc) DBM, as well as LC10- and LC50-dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 46 publications
0
8
1
Order By: Relevance
“…The botanical insecticide azadirachtin significantly reduced the number of haemocytes in the reduviid, Rhodnius prolixus (Azambuja et al, 1991). fenvalerate and methomyl (Sota et al, 1998), and the phosphorothioate insecticides chlorpyrifos (Deng et al, 2016). Our experiment, however, revealed an opposite trend, which enhanced the insect immune function, and may be a concurrent hormesis.…”
Section: Discussioncontrasting
confidence: 44%
See 2 more Smart Citations
“…The botanical insecticide azadirachtin significantly reduced the number of haemocytes in the reduviid, Rhodnius prolixus (Azambuja et al, 1991). fenvalerate and methomyl (Sota et al, 1998), and the phosphorothioate insecticides chlorpyrifos (Deng et al, 2016). Our experiment, however, revealed an opposite trend, which enhanced the insect immune function, and may be a concurrent hormesis.…”
Section: Discussioncontrasting
confidence: 44%
“…A few studies in recent years have demonstrated that some organophosphate, botanical and IGR pesticides have been shown to reduce the effects on insect immunity through affecting either the PO activity or the haemocyte activity (George & Ambrose, 2004;Ma et al, 2008;Nasr et al, 2010). In the diamond moth (Plutella xylostella), a sublethal dose of chlorpyrifos was found substantially to increase the activity of several enzymes, such as acetylcholinesterase and glutathione S-transferases (Deng et al, 2016). Hormesis is a dose-response phenomenon, which is the most fundamental dose response in the biomedical and toxicological sciences, characterised by a low-dose stimulation and high-dose inhibition (Calabrese & Baldwin, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This might be because of the effect of sublethal concentrations and/or interaction of chlorpyrifos and imidacloprid. Several studies report adaptive responses subsequent to exposure to sublethal concentrations of chemical pesticides (Zanuncio et al, 2005;Deng et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies have been conducted to show the effect of temperature on synthetic insecticides susceptibility, the alteration in entomopathogenic fungi pathogenicity due to changes in temperature was not understood (Deng, Zhang, Wu, Yu, & Wu, ; Garcia et al., ; Lasa, Williams, & Caballero, ; Zhang et al., ). However, susceptibility to entomopathogenic fungi was increased in Las‐infected as compared to uninfected D. citri , but Las infection did not affect the correlation coefficients between temperature and psyllids mortality.…”
Section: Discussionmentioning
confidence: 99%